Political Election Debates: Informing Voters about Policy and Character - Benoit, William L. (Lexington Books, 2013)
Political debates are an important facet of modern election campaigns. How politicians frame an argument, how the audience perceives it, and how the media decides to display it are key components in analyzing the outcome of a political debate, and ultimately, an election. Drawing mainly on the functional theory of political campaign discourse, William L. Benoit examines a wide variety of debates not only in the United States but across the globe. Because each phase of election offers new challenges, specific attention is paid to how primary versus general and incumbency influence the content of political leaders’ debate practices. Specifically, the book delves into the history and nature of debates in various United States elections, including presidential, vice presidential, senatorial, gubernatorial, and mayoral candidates. Also examined are debates ranging from the United Kingdom to South Korea to Australia. Benoit also employs the issues ownership theory and functional federalism theory as a deeper part of the analysis. This book offers a critical examination and comprehensive overview of election debate theory.